Neuronal Calcium and cAMP Cross-Talk Mediated by Cannabinoid CB1 Receptor and EF-Hand Calcium Sensor Interactions - Angelats, Edgar; Requesens, Marta; Aguinaga, David; Kreutz, Michael R.; Franco, Rafael; Navarro, Gemma (Frontiers in Cell and Developmental Biology, 2018)
Endocannabinoids are important players in neural development and function. They act via receptors, whose activation inhibits cAMP production. The aim of the paper was to look for calcium- and cAMP-signaling cross-talk mediated by cannabinoid CB1 receptors (CB1R) and the relevance of EF-hand CaM-like calcium sensors in this regard. Using a heterologous expression system, we demonstrated that CB1R interacts with calneuron-1 and NCS1 but not with caldendrin. Furthermore, the first two sensors competed for binding to the receptor in a Ca2+-dependent manner. Assays in neuronal primary cultures showed that, CB1R-NCS1 complexes predominate at basal Ca2+ levels, whereas in the presence of ionomycin, a calcium ionophore, CB1R-calneuron-1 complexes were more abundant. Signaling assays following forskolin-induced intracellular cAMP levels showed in mouse striatal neurons that binding of CB1R to NCS1 is required for CB1R induced signaling while the binding of CB1R to calneuron-1 is completely blocked signaling in response to a selective receptor agonist, arachidonyl-2-chloroethylamide.